The Rational of Colloid Requirements in Burn Patients : Literature Reviews - Wardhana, Aditya; Septrisya, Shiera (Lingkar Studi Bedah Plastik Foundation, 2012)
Backgrounds: For decades, fluid resuscitation in burn patients has been done as a routine process; most clinicians continue to adjust volume requirements using Parkland formula for the initial 24- hour period. In a variety of situations, there is increasing recognition of using significantly greater volumes than anticipated by the Parkland formula; clinicians tend to escalate volume requirements to drive the urine output to the higher end of any desired range. This excessive fluid could result in numerous edema-related complications, which currently coined as “fluid creep” phenomenon. Besides optimizing titration of fluid infusion rate, there have been studies of earlier and more liberal use of colloids, and even the use of hypertonic saline. The overall goal is to reduce the resuscitation volume requirements and subsequently, early edema formation.Conclusion: Current research in fluid resuscitation now concentrates on approaches to minimize fluid creep, including tighter control of fluid infusion rate. The single most important principle in using the Parkland formula, however, is that it should be used only as a guideline. The resuscitation rate and volume must be continually adjusted based on the response of the patient. Studies have been demonstrated to compare the use of crystalloids with early colloid in the first 24 hours post burn. At present, there are still wide variations in the timing of colloid resuscitation. However, use of 5% albumin in the second 24 hours seems to be an acceptable alternative.